Tecnologías aplicadas para la elaboración de productos con valor agregado a partir de arroz (Oryza sativa L. - García Nieto, Gustavo Andrés (2024)
Based on the development of the study, the main topic has been considered as "Applied technologies for the production of value-added products from rice (Oryza sativa L.)" in which it was established as a general objective, to analyze the technologies applied for the production of value-added products from rice. It was proposed as a methodology in this research document presented as a practical component, it was developed through the collection of all types of information, according to research techniques. The methodology used in this study was exploratory and explanatory. In results, the research revealed that advanced milling technologies, such as friction milling and cryogenic grinding, are used to obtain high-quality rice flours, these technologies make it possible to control the particle size size, thus improving the texture and versatility of flours, which are used in bread making, cakes and bakery products. In conclusion, it is detailed that the technologies applied in the production of value-added products from rice are crucial for the diversification and improvement of the quality of the products, where the importance of techniques such as advanced milling and extrusion is highlighted.